Analysis of the impact of the construction sector on Colombian economy - Jorge Andrés Sarmiento-Rojas (Tecnura, 2020)
Objective Construction is one of the fastest growing and most important economic sectors worldwide, mainly due to its impact on job creation, trade in materials and the creation of essential infrastructure for social development. However, the behavior of the global market has recently been immersed in an environment of economic and political uncertainty, causing trade and industrial production to show signs of vulnerability. Despite the unfortunate ones established in the global economy, there will be moderate growth in rankings of developing countries like Colombia in different sectors.Methodology This research focuses on analyzing the construction sector. The analysis is carried out from its historical impact on Colombian economic development and its relationship with external phenomena, to the evaluation of macroeconomic indicators (supply and demand), infrastructure, and job creation through the formulation of projects in this sector. In particular, these projects are differential for having a public investment effect in the construction of houses and civil works.Results and Conclusions It was concluded that there is a weak recovery in the general market in relation to the factors surrounding the construction sector, allowing for a glimpse and focus on the trends and impact on the formulation of construction projects in the Colombian economy.